Problem postcards social, emotional and behavioural skills training for disaffected and difficult children aged 7 to 11 - Koeries, Janine; Marris, Brian; Rae, Tina.; Cripps, Mark.; Sage eBooks (London : Paul Chapman, 2005)
This 14 session programme was initially developed for junior age children who had been permanently excluded. It has been adapted to assist young people who are disaffected & difficult, & could be at risk of exclusion.
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: Problem children -- Education; Social skills -- Study and teaching (Elementary); Emotional intelligence -- Study and teaching (Elementary); Problem children -- Education; Social skills in children; Electronic books